Meaning-making while staying connected matters in psychological adaptation during pandemic: a longitudinal moderated mediation study - Kim, Bin-Na; Kang, Hyo Shin; Park, Jungkyu (Frontiers in Psychology, 2024)
Adversity may bring about both negative and positive changes in psychological adaptation. Although there is mounting evidence regarding the psychological distress during the pandemic, the other side of posttraumatic change, posttraumatic growth (PTG) and its predictors are relatively underexamined. Moreover, there is a paucity of longitudinal investigations that examined intra- and interpersonal predictors responsible for both sides of psychological adaptation. Therefore, this study comprehensively examined the longitudinal relationship among cognitive processing, social support, and adaptation during the pandemic using a moderated mediation model. Specifically, it was tested whether two types of event-related rumination mediated the link between perceived stress and ambilateral adaptational outcomes, and whether social support moderated the mediating pathways of ruminations on adaptation. After informed consent, a representative sample of adults was followed up for over a year, and answered a package of online questionnaires. The results showed that intrusive rumination prospectively predicted greater psychological distress and less PTG in response to stress, whereas deliberate rumination led to less psychological distress and more PTG over time. As predicted, the indirect protective effect of deliberate rumination was stronger when perceived social support was higher. This longitudinal study highlighted the core factors responsible for continued suffering and personal growth during the pandemic. These results have both practical and clinical implications for mental healthcare in the post-COVID era, when the heterogeneity of psychological adaptation increases and preparation for the next pandemic is warranted.